2015
DOI: 10.1186/s13071-015-0747-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phage Display technology in development of canine visceral leishmaniasis vaccine using synthetic peptide trapped in sphingomyelin/cholesterol liposomes

Abstract: Background: Leishmania parasites can cause visceral or cutaneous disease and are found in subtropical and tropical regions of the Old and New World. The pathology of the infection is determined by both host immune factors and species/strain differences of the parasite. Dogs represent the major reservoir of Leishmania infantum (syn. L. chagasi) and vaccines are considered the most cost-effective control tools for canine disease. Methods: Selection of immunodominant peptides was performed by Phage Display to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…In fact, evaluating peptides ELISA assays, high sensitivity values were observed, that ranging from 82.86–100.00%, included peptide mixtures (Mix I, II, III and IV), and can be explained by high expression in intracellular stages, subcellular localization (secreted/excreted) and high antigenicity demonstrated by B-cell prediction. In according, previous studies have demonstrated that proteins expressed in stages found in vertebrate host are possibly associated with with the infection process and/or the intracellular survival of the parasite within the host, and may be attractive diagnostic targets [30, 45, 49]. Serological tests have also presented limitations regarding the absence of correlation between the antibody levels and the current stage of the disease [21, 50].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, evaluating peptides ELISA assays, high sensitivity values were observed, that ranging from 82.86–100.00%, included peptide mixtures (Mix I, II, III and IV), and can be explained by high expression in intracellular stages, subcellular localization (secreted/excreted) and high antigenicity demonstrated by B-cell prediction. In according, previous studies have demonstrated that proteins expressed in stages found in vertebrate host are possibly associated with with the infection process and/or the intracellular survival of the parasite within the host, and may be attractive diagnostic targets [30, 45, 49]. Serological tests have also presented limitations regarding the absence of correlation between the antibody levels and the current stage of the disease [21, 50].…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenic peptides (selected in this work by spot synthesis) plus three peptides previously selected by our research group (selection determined by phage display and hypersensitivity reaction named P1, P2, and P3 for detail, see Link et al, 2017 ; Guedes et al, 2019 ), were encapsulated in liposome according to Toledo-Machado et al ( 2015 ), producing the peptide-based antigen. Briefly, the encapsulated peptides were produced by dissolving sphingomyelin (25 mg) and cholesterol (6.5 mg) in 5 mL solution containing methanol and chloroform (1:2).…”
Section: Methodsmentioning
confidence: 99%
“…These peptides presented high performance and sensitivity, either alone or in combination, indicating that they may have applications in the immunoprotection against or diagnosis of leishmaniasis. 41 Canis lupus familiaris is an important reservoir of Leishmania infantum, and a novel peptide was identified that showed a promising capability to promote a state of active immunity against L infantum infections in mice after immunized using liposomes as a vaccine vehicle, 42 The abovementioned findings reveal a promising health care target with respect to the serodiagnosis and development of vaccines against Leishmania parasites.…”
Section: Parasitic Infectious Diseasesmentioning
confidence: 99%